Bunuh Diri Dalam Perspektif Ensklik Evangelium Vitae Paus Yohanes Paulus II - Koli, Arnoldus Nofrianus; Bria, Zakharias; Karloman, Siprianus (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The Encyclical Evangelium Vitae by Pope John Paul II affirms that human life is a sacred and irreplaceable gift from God. In this document, the Pope condemns the practice of suicide as a direct attack on life, which is the prerogative of God as the Creator and SustainerIt is explained that suicide is a rejection of divine love and a denial of the dignity and value of human life. This Encyclical emphasizes that human life must be respected and protected from conception to natural death.Suicide is seen as an act that is contrary to the human vocation to be the image and likeness of God, and to fulfill the mission of safeguarding and preserving life. The Pope calls on the faithful to provide support and compassion to those who are trapped in depression or existential crisis, so that they can rediscover the meaning and purpose of their lives. Overall, Evangelium Vitae asserts that any form of destruction or destruction of human life is a violation of the dignity and human rights granted by God. Suicide is seen as a morally unjustifiable act, and the Church is committed to protecting and promoting a culture of life that is in accordance with God's plan of love.